MULTIMODAL ANALYSIS OF VERBAL AND VISUAL ELEMENTS IN THE DAY YOU BEGIN - Zarah Khodijah Yasmin; Rangkuti, Rahmadsyah; Putri, Dian Marisha; Lubis, Tasnim; Harefa, Yulianus (Linguistics and Literature Journal, 2025)
This study examined the verbal and visual elements in the children’s picture book The Day You Begin (2018) by Jacqueline Woodson, illustrated by Rafael López, and explored how these intermodal connections conveyed the theme of diversity. A qualitative design was employed, utilising 14 data units, each comprising one verbal excerpt and its corresponding illustration, purposively selected from 28 narrative pages. The data were gathered through reading, identifying pages that portrayed diversity, selecting units, transcribing verbal texts, describing illustrations, and pairing them for analysis. The analysis drew on Halliday and Matthiessen’s (2014) Systemic Functional Linguistics, Kress and van Leeuwen’s (2006) Visual Grammar, and Painter et al.’s (2013) theory of intermodal coupling. Through data condensation, display, and conclusion drawing, the study examined ideational, interpersonal, and textual meanings. The findings showed that verbal and visual elements consistently expressed ideas of difference, belonging, and identity. Their intermodal couplings were largely convergent, reinforcing the theme of diversity. The study concluded that the integration of verbal and visual meanings represented experiences of diversity and identity through metafunctional realizations, while their convergent couplings emphasized empathy, inclusion, and acceptance of differences.Keywords: intermodal coupling, multimodal analysis, picture book, verbal-visual elements